Komunikasi Singkat: Jenis temu-temuan yang dijual di Pasar Badung, manfaat, serta anatominya - Darsini, Nyoman (Jurnal Biologi Udayana; Vol 26 No 2 (2022): JURNAL BIOLOGI UDAYANA, 2022)
Research has been carried out on the temu-temuan or bebungkilan conducted in Pasar Badung, with a research method through the interview method. Based on research techniques interviews with 5 merchants, 10 temu-temuan have been found. The types of temu-temuan that have been found are: temu kunci, curcuma, temu ireng, galangal, aromatic ginger, jangu, turmeric, bangle, red ginger, temu tis.  Morphologically, each temu-temuan has its own characteristics, while in its anatomy it appears that the secretory cell is scattered randomly.  The benefits of these temu-temuan are partly as a medicine and partly as a kitchen spice. Especially in Bali, which is often used as a basic spice, is turmeric, aromatic ginger, ginger and galangal. As for other temu-temuan such as, temu ireng, temu kunci, curcuma, bangle besides turmeric, aromatic ginger, ginger, galangal with medicinal properties. The benefits of these findings for health, ranging from overcoming gastrointestinal infections, skin diseases, healing wounds, antioxidants, anticancer, curing stomach ulcers, delaying premature aging, lowering levels of bad cholesterol, cough and asthma, menstrual disorders, dyspepsia, body warmers, swollen ulcers, preventing cancer, relieving seizures, and much more.